รูปแบบการบริหารจัดการพลังงานทางเลือกระดับตำบลอย่างมีส่วนร่วม เทศบาลตำบลคำขวาง อำเภอวารินชำราบ จังหวัดอุบลราชธานี - โสภาพล, สุขวิทย์ (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ The Model of Participatory Management of Alternative Energy at Sub-district level, Kham Khwang Municipal Sub-district, Warin Chamrap District, Ubon Ratchathani Province The objective of this research was to seek for the cooperative management model of alternative energy utilization and productivity of Kham Khwang community (Sub-district) that match to context and resources of the community. The research was conducted during the year 2556-2557 using qualitative and quantitative research methodology. The sample group of 310 in this research was randomized from 10 villages in Kham Khwang. The qualitative methodology of this research was participatory action research including several steps of the research activities. The research tools were questionnaires, survey, and practicing/experiment record and participatory observation. The processes of the research divided into 4 phases 1) pre-preparation: research team preparing and research conducting planning 2) preparation: reviewing of concepts and theory related to the research, community and community leaders meeting for research explanation, volunteers recruiting for alternative energy practices/experiment and data analyzing 3) implementing: meeting for knowledge conclusion and setting of the model for the alternative energy practicing/experiment, meeting with the community and community administrators to set the experiment model then conduct the experiment follow the set model 4) conclusion and assessment: meeting for conclusion of learning at the household level and sub-district level, knowledge extension and community cooperation. The result of the research showed that the alternative energy participatory management model of Kham Khwang Sub-district could be explained into 2 parts 1) holistic management of 7 phases: understanding and motivating, problems and need realizing, decision making, preparing, operating, instrument and operation maintaining and monitoring 2) production management: input management, processes management, output management and outcome management. This research found that the suitable alternative energy for Kham Khwang Sub-district was solar cell and buffalo dung biogas.